2006
DOI: 10.1111/j.1365-313x.2006.02931.x
|View full text |Cite
|
Sign up to set email alerts
|

ATR and ATM play both distinct and additive roles in response to ionizing radiation

Abstract: SummaryThe ATR and ATM protein kinases are known to be involved in a wide variety of responses to DNA damage. The Arabidopsis thaliana genome includes both ATR and ATM orthologs, and plants with null alleles of these genes are viable. Arabidopsis atr and atm mutants display hypersensitivity to c-irradiation. To further characterize the roles of ATM and ATR in response to ionizing radiation, we performed a short-term global transcription analysis in wild-type and mutant lines. We found that hundreds of genes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
408
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 289 publications
(436 citation statements)
references
References 42 publications
26
408
1
1
Order By: Relevance
“…Previously, it was found that CYCB1;1 upregulation depends on ATM and SOG1 (Culligan et al , 2006; Yoshiyama et al , 2009). To test therefore whether CYCB1;1 and CDKB1s are directly regulated by SOG1, we performed ChIP experiments with plants expressing a tagged SOG1 version grown on cisplatin.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, it was found that CYCB1;1 upregulation depends on ATM and SOG1 (Culligan et al , 2006; Yoshiyama et al , 2009). To test therefore whether CYCB1;1 and CDKB1s are directly regulated by SOG1, we performed ChIP experiments with plants expressing a tagged SOG1 version grown on cisplatin.…”
Section: Resultsmentioning
confidence: 98%
“…Arabidopsis thaliana atm mutants display chromosomal fragmentation in most meiocytes, leading to reduced fertility (Garcia et al, 2003). atr mutant plants, by contrast, are fully fertile, but atm atr double mutants are completely sterile, because of severe chromatin fragmentation (Culligan et al, 2004;Culligan et al, 2006;Culligan and Britt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ATM (Yoshiyama et al, 2013) and inferably ATR (Furukawa et al, 2010;Yoshiyama et al, 2009) can phosphoactivate the transcription factor SOG1, as well as other proteins, in plant cells (Roitinger et al, 2015;Yoshiyama et al, 2013). Once activated, SOG1 transcriptionally induces various functional classes of DDR genes (Yoshiyama et al, 2009;Missirian et al, 2014;Ricaud et al, 2007); SOG1 induces a robust set of .100 transcripts by $4-fold within 1.5 h in response to 100 Gy IR (Culligan et al, 2006;Furukawa et al, 2010). SOG1 has a known role in transcriptionally inhibiting cell cycle progression in response to DNA damage (Preuss and Britt, 2003;Yoshiyama et al, 2009).…”
mentioning
confidence: 99%
“…A plant cell's response to DNA damage first involves the DSB-detecting protein kinase ATM (AtaxiaTelangiectasia-Mutated) or the detector of stalled replication forks ATR (Ataxia Telangiectasia Mutated and Rad3-related protein; Culligan et al, 2006;Furukawa et al, 2010). ATM (Yoshiyama et al, 2013) and inferably ATR (Furukawa et al, 2010;Yoshiyama et al, 2009) can phosphoactivate the transcription factor SOG1, as well as other proteins, in plant cells (Roitinger et al, 2015;Yoshiyama et al, 2013).…”
mentioning
confidence: 99%